61.0k views
1 vote
Please help me!!!!!​ i need full answer.

Please help me!!!!!​ i need full answer.-example-1

1 Answer

3 votes

Answer:

see explanation

Explanation:

Using the sum/ difference → product formula

cos x - cos y = - 2sin(
(x+y)/(2))sin (
(x-y)/(2) )

sin x - sin y = 2cos (
(x+y)/(2) )sin (
(x-y)/(2) )

Given

(cosA - cosB)² + (sinA - sinB )²

= [ - 2sin(
(A+B)/(2))sin(
(A-B)/(2) ) ]² + [ 2cos(
(A+B)/(2) )sin(
(A-B)/(2) ) ]²

= 4sin² (
(A+B)/(2) )sin² (
(A-B)/(2) ) + 4cos² (
(A+B)/(2) )sin² (
(A-B)/(2) )

= 4sin² (
(A-B)/(2) )[ sin² (
(A+B)/(2) ) + cos² (
(A+B)/(2) ) ← sin²x + cos²x = 1

= 4sin² (
(A-B)/(2) ) × 1

= 4sin² (
(A-B)/(2) ) = right side ⇒ proven

User Michael Zilbermann
by
5.3k points